Dermato-Surgical Approach In Vitiliogo - Malakar Subrata (Wolters Kluwer Medknow Publications, 1995)
Vitiligo is a hypomelanotic disorder often difficult to treat. Different medicinal treatments such as PUNA, steroids and adjunct theraples give partial or complete repigmentation in about 60-90% cases. Moreover, vitiligo patches which are refractory to most medical therapies are acrofacial, mucosal and segmental. At the backdrop of these medicinal shortcomings, various surgical procedures and their modifications have gradually evolved. To decide why, where and when surgical interference is required, is of utmost importance. In this review different surgical modes, including some of the latest, and their future prospects are discussed.